Kolaborasi Kampanye Rangkoel Care Indonesia dengan Blishful Lipcare tentang Kesehatan Mental - Daffa Aprillian; Maya Amalia Oesman Palapah (Bandung Conference Series: Public Relations, 2024)
Abstract. According to the Indonesian National Health Research (RISKESDAS, 2013), approximately 9 million people, out of a population of 250 million, are affected by depression. Additionally, about 14 million individuals aged 15 years and older experience temperament disorders such as depression and anxiety. Yayasan Rangkoel Care Indonesia aims to assist the younger generation in raising awareness about mental health by employing a strategy that involves transforming one's mental or emotional unrest into a work of art. In collaboration with Blishful Lipcare, Yayasan Rangkoel Care Indonesia engages in the distribution of artwork through the Self Love campaign. This campaign serves as an encouragement for individuals to prioritize self-love and mental health. The research adopts a constructivist paradigm, utilizing qualitative methods and a case study approach. Data collection techniques include in-depth interviews, observation, and documentation. Key informants include the chairman of Yayasan Rangkoel Care Indonesia and the Marketing Department of Yayasan Rangkoel Care Indonesia, while on the Blishful Lipcare side, the subject is Research and Development. Data analysis employs techniques of data reduction, presentation, and verification. Source triangulation is employed as a method to ensure data validity by comparing and re-examining information across different times and tools in qualitative methods. There are findings that. 1).The collaboration of Rangkoel Care Indonesia together with Blishful Lipcare occurs in the fusion of two vision and mission between institutions, namely profit and non-profit. 2).Yayasan Rangkoel Care Indonesia made a collaboration innovation in the form of a Self Love campaign to Blishful Lipcare legally sending Offering Partnership, until the execution of the Self Love campaign was carried out based on the tasks that had been shared between Yayasan Rangkoel Care Indonesia and Blishful Lipcare and closed by evaluating the campaign by both parties. 3) Vision & mission are in line with having attention to Indonesia's mental health, the popularity of Blishful Lipcare is felt to be able to provide high exposure to the Rangkoel Care Indonesia Foundation, and the beauty field is able to become a medium of art and lifting confidence so that it can lift each other's Brand Image. Abstrak. Prevalensi Masalah Kesehatan Mental Menurut Riset Kesehatan Nasional Indonesia (RISKESDAS,2013), sekitar 9 juta orang menderita depresi, dari populasi 250 juta orang. Sekitar 14 juta orang berusia 15 tahun ke atas menderita gangguan temperament seperti depresi dan kecemasan. Yayasan Rangkoel Care Indonesia hadir berupaya untuk membantu para generasi muda agar meningkatkan kesadaran akan kesehatan mental dengan strategi yang digunakan adalah berusaha mengkonversi keresahan mental atau emosi seseorang menjadi sebuah karya seni. Dalam hal ini, Yayasan Rangkoel Care Indonesia berkolaborasi dengan Blishful Lipcare sebagai distribusi karya seni dengan kampanye Self Love. Kampanye ini sebagai bentuk dorongan terhadap seseorang agar lebih mencitai dirinya sendiri dan lebih memperhatikan kesehatan mental. Paradigma yang diterapkan dalam penelitian ini merupakan paradigma konstruktivistik, dengan metode kualitatif dan pendekatan studi kasus. Wawancara mendalam, observasi dan dokumentasi dipilih sebagai teknik pengumpulan data. Wawancara mendalam dilakukan kepada informan seperti, ketua dari Yayasan Rangkoel Care Indonesia, Marketing Departement Yayasan Rangkoel Care Indonesia sedangkan di pihak Blishful Lipcare terdapat subjek yaitu Research and Development. Reduksi, penyajian dan verifikasi data dipilih sebagai teknik analisi data peneltian. Begitu pula dengan trigulasi sumber, dipilih sebagai cara uji keabsahan data melalui membandingkan dan memeriksa kembali keadaan informasi pada waktu dan alat yang berbeda dalam metode kualitatif. Tedapat temuan bahwa. 1).Kolaborasi Rangkoel Care Indonesia bersama dengan Blishful Lipcare terjadi pada peleburan dua visi misi antar Lembaga yaitu profit dan non profit. 2).Yayasan Rangkoel Care Indonesia membuat inovasi kerjasama berupa kampanye Self Love kepada Blishful Lipcare secara legal mengirim Offering Partnership, hingga eksekusi kampanye Self Love pun dilakukan berpatok kepada tugas yang sudah dibagikan antara Yayasan Rangkoel Care Indonesia bersama Blishful Lipcare dan ditutup oleh evaluasi kampanye oleh kedua belah pihak. 3) Visi & misi sejalan memiliki atensi terhadap kesehatan mental Indonesia, popularitas Blishful Lipcare dirasa mampu memberikan Exposure tinggi kepada Yayasan Rangkoel Care Indonesia, serta bidang kecantikan mampu menjadi medium seni dan pengangkatan kepercayaan diri sehingga mampu mengangkat Brand Image satu sama lain.